Highlights of IFPRI's partnerships and impacts in China 2015: Reducing poverty and hunger through food policy research - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
For more than 30 years, China has undergone economic reforms and development that have led to successful economic growth and poverty reduction. The country has also made considerable efforts to reduce the income gap between urban and rural populations, balance regional development, and conserve natural resources. In 2003, IFPRI developed a strategy specifically tailored to its work in China and expanded its national program. In collaboration with the Chinese Academy of Agricultural Sciences (CAAS), IFPRI established the International Center for Agricultural and Rural Development (ICARD) that same year to coordinate the Institute’s propoor research and activities in China and East Asia.